Photophysical, Photochemical, and BQ Quenching Properties of Zinc Phthalocyanines with Fused or Interrupted Extended Conjugation - Gülşah Gümrükçü; Gülnur Keser Karaoğlan; Ali Erdoğmuş; Ahmet Gül; Ulvi Avcıata (Journal of Chemistry)
The effects of substituents and solvents on the photophysical and photochemical parameters of zinc(II) phthalocyanines containing four Schiff’s base substituents attached directly and through phenyleneoxy-bridges on peripheral positions are reported. The group effects on peripheral position and the continual and intermittent conjugation of the phthalocyanine molecules on the photophysical and photochemical properties are also investigated. General trends are described for photodegradation, singlet oxygen, and fluorescence quantum yields of these compounds in dimethylsulfoxide (DMSO), dimethylformamide (DMF), and tetrahydrofurane (THF). Among the different substituents, phthalocyanines with cinnamaldimine moieties (1c and 2c) have the highest singlet oxygen quantum yields (ΦΔ) and those with nitro groups (1a and 2a) have the highest fluorescence quantum yields in all the solvents used. The fluorescence of the substituted zinc(II) phthalocyanine complexes is effectively quenched by 1,4-benzoquinone (BQ) in these solvents.